Suppression of boron incorporation at the early growth phases of boron‐doped diamond thin films. Issue 11 (22nd July 2015) - Tsigkourakos, Menelaos; Hantschel, Thomas; Xu, Zheng; Douhard, Bastien; Meersschaut, Johan; Zou, Yiming; Larsson, Karin; Boman, Mats; Vandervorst, Wilfried
Abstract : The presence of O during the chemical vapour deposition (CVD) of B‐doped diamond results in the suppression of B incorporation into the diamond film. In this study, we demonstrate that the amount of residual O within the chamber is higher at the beginning of the diamond growth due to the O‐contaminated chamber walls, and is decreased after a certain time period. This leads to a gradual increase of the B incorporation by more than one order of magnitude during the early growth phases of nanocrystalline diamond (NCD). We further show that this suppression of B incorporation at the early growth phases of B‐doped diamond is influenced by the growth rate of the film. This is attributed to the constant time period whereby most of the residual O interacts with the B‐precursors in the gas phase by forming stable B–O species, which are flushed out from the chamber exhaust. Furthermore, the constant B profile of an NCD film grown in a loadlock hot‐filament CVD (HFCVD) system reveals that the amount of residual O is constant and minimal during the growth process. Therefore, our work proves that the use of a loadlock overcomes the B‐suppression problem at the early growth phases of diamond, making it the optimal solution for the growth of highly conductive thin diamond films.